VITAMIN MINERAL COMPLEXES FOR CHILDREN IN THE PERIOD OF ACTIVE SOCIAL ADAPTATION - V. M. Kodentsova; D. V. Risnik (Медицинский совет, 2018)
The subnormal vitamin deficiency form poses a threat to the normal growth and development of the child. Reduced supply of vitamins A, PP, B6, B12, E is associated with decreased immunity, and increases the risk of physical development delay and the formation of functional diseases. According to 2015--2017 data, the vitamin provision pattern for preschool and school children is almost the same regardless of the place of their residence: only one in four or five children are provided by all vitamins. Up to 50% of children suffer from polyhypovitaminosis, (i.e., a deficiency of 3 or more vitamins). In the settings of insufficient production of food products enriched with vitamins, the main way to eliminate vitamin deficiency is the use of vitamin mineral complexes. The inter-vitamin interactions and the high incidence of polyhypovitaminosis conditions among the children give occasion to use the vitamin mineral complexes (VMCs). The intake of VMCs is more efficient in comparison with the use of monovitamins. When choosing an VMC for children, one should give preference to complexes containing a full set of vitamins to be taken in an amount comparable with the age recommended intake, and mineral substances, which deficit is most often found in the population of Russia. The systematic consumption of food products enriched with vitamins and/or VMCs results in increased levels of vitamins in blood plasma, a decreased frequency of polyhypovitaminosis, increased number of children adequately provided with all the vitamins.